SIMPLIFY -9.2+6.5

Guide :

SIMPLIFY -9.2+6.5

SIMPLIFY, -9.2+6.5

Research, Knowledge and Information :


Simplify radical,rational expression with Step-by-Step Math ...


simplify rational or radical expressions with our free step-by-step math calculator ... Simplifying Polynomials. ... 2 = 25 and ( - 5) 2 = 25.
Read More At : quickmath.com...

Mathway | Simplify 9 2/6-6 5/6


Free math problem solver answers your algebra, geometry, trigonometry, calculus, and statistics homework questions with step-by-step explanations, just like a math tutor.
Read More At : www.mathway.com...

Simplifying Fractions - Math Is Fun


Simplifying Fractions. To simplify a fraction, ... Try to evenly divide (only whole number answers) both the top and bottom of the fraction by 2, 3, 5, 7 , ...
Read More At : www.mathsisfun.com...

Simplify any Algebraic Expression - WebMath


Simplify any Algebraic Expression ... If you have some tough algebraic expression to simplify, this page will try everything this web site knows to simplify it.
Read More At : www.webmath.com...

Simplify (5x)/6 +(3x)/2 - Simplify Calculator - Symbolab


Free simplify calculator - simplify algebraic expressions step-by-step
Read More At : www.symbolab.com...

Simplify the expression. 6(3 · 9 - 2 · 9) + 6(7 · 9 - 5 · 9)?


Simplify the expression. 6(3 · 9 - 2 · 9) + 6(7 · 9 - 5 · 9)? Find answers now! No. 1 Questions & Answers Place. More questions about Science & Mathematics
Read More At : www.weknowtheanswer.com...

How do you simplify 5/6(-12)+2/3(9)-7/12(24)? | Socratic


How do you calculate the theoretical yield of aspirin given that 3.52mL of acetic anhydride was ...
Read More At : socratic.org...

NumberNut.com: Fractions and Decimals: Fractions: Addition


Basic Steps of Adding Fractions ... • Write out the mixed number: 6 5/9 • Simplify: 5/9 can't be simplified. You are done. Answer: 2 2/9 + 4 3/9 = 6 5/9
Read More At : www.numbernut.com...

Simplify. (a6b7)6 - Algebra homework help


Simplify. (a6b7)6. All work must be ... Must be in APA format. Must be done by 02/23/2014 by 12pm EST. 1. Simplify. (a 6 b 7) 6 2. ... y 7 + y 6 + 8y 5 + 2 ...
Read More At : www.homeworkmarket.com...

Suggested Questions And Answer :


sqrt(3a+10) = sqrt(2a-1) + 2

sqrt(3a+10)=sqrt(2a-1)+2 To remove the radical on the left-hand side of the equation, square both sides of the equation. (~(3a+10))^(2)=(~(2a-1)+2)^(2) Simplify the left-hand side of the equation. 3a+10=(~(2a-1)+2)^(2) Squaring an expression is the same as multiplying the expression by itself 2 t
Read More: ...

how to solve for x with fractions

Simplifying x3 + 3x2 + -4x = 0 Reorder the terms: -4x + 3x2 + x3 = 0 Solving -4x + 3x2 + x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), 'x'. x(-4 + 3x + x2) = 0 Factor a trinomial. x((-4 + -1x)(1 + -1x)) = 0 Subproblem 1 Set the factor 'x' equal to zero an
Read More: ...

Whats 3x-2 over 9 equals 25 over 3x-2?

I will give you an example for this question. This might be able to help you. Simplifying 3x2 + 25x = 18 Reorder the terms: 25x + 3x2 = 18 Solving 25x + 3x2 = 18 Solving for variable 'x'. Reorder the terms: -18 + 25x + 3x2 = 18 + -18 Combine like terms: 18 + -18 = 0 -18 + 25x + 3x2 = 0 Fac
Read More: ...

(13-3)x5=50

Simplifying x + 2 = 3x + -1x2 + 5 Reorder the terms: 2 + x = 3x + -1x2 + 5 Reorder the terms: 2 + x = 5 + 3x + -1x2 Solving 2 + x = 5 + 3x + -1x2 Solving for variable 'x'. Reorder the terms: 2 + -5 + x + -3x + x2 = 5 + 3x + -1x2 + -5 + -3x + x2 Combine like terms: 2 + -5 = -3 -3 + x + -3x + x2
Read More: ...

(8x)[(2x)^-2=8

Simplifying 8x = 2x2 + 8 Reorder the terms: 8x = 8 + 2x2 Solving 8x = 8 + 2x2 Solving for variable 'x'. Reorder the terms: -8 + 8x + -2x2 = 8 + 2x2 + -8 + -2x2 Reorder the terms: -8 + 8x + -2x2 = 8 + -8 + 2x2 + -2x2 Combine like terms: 8 + -8 = 0 -8 + 8x + -2x2 = 0 + 2x2 + -2x2 -8 + 8x + -2x2
Read More: ...

what is the answer for x/7+4=x/7

(x)/(7)+4=(x)/(7) Multiply each term in the equation by 7. (x)/(7)*7+4*7=(x)/(7)*7 Simplify the left-hand side of the equation by canceling the common terms. x+28=(x)/(7)*7 Simplify the right-hand side of the equation by simplifying each term. x+28=x Since x contains the variable to solve for, m
Read More: ...

Write out the solution to the equation : x + y - z = 0, 2x + 4y - z = 0 and 3x + 2y + 2z = 0

first equation: x + y - z = 0 x + y = z in the other 2 equations, replace z with x + y: 2x + 4y -(x+y) = 0 3x + 2y +2(x+y) = 0 simplify: 2x + 4y -x -y = 0 3x + 2y +2x +2y = 0 simplify more: x + 3y = 0 5x + 4y = 0 in the top equation, move the 3y to the other side: x = -3y in the bottom
Read More: ...

find a particular solution (e^x+y +ye^y)dx+(xe^y -1)dy=0 if y(0)=-1

This has the form of an exact DE. Let's see if it is.  First rewrite: (e^x+y+ye^y)+(xe^y-1)dy/dx=0=A(x,y)+B(x,y)dy/dx=0 where A=e^x+y+ye^y and B=xe^y-1. (p.d.=partially differentiate; wrt=with respect to)   Take A and p.d. wrt y=1+ye^y+e^y (a) Take B and p.d wrt x=e^y (b) S
Read More: ...

simplify 6x/x+3=9/x-3-15/x^2-9

  6x / (x + 3) = [9 / (x - 3)] - [15 / (x^2 - 9)] 6x(x - 3) / (x + 3)(x - 3) = [9(x + 3) / (x + 3)(x - 3)] - [15 / (x^2 - 9)] (6x^2 - 18x) / (x^2 - 9) = [(9x + 27) / (x^2 - 9)] - [15 / (x^2 - 9)] 6x^2 - 18x = 9x + 27 - 15 6x^2 - 18x - 9x - 12 = 0 6x^2 - 27x - 12 = 0
Read More: ...

how would you simplify this expression (1/y)+(2/7)-(3/2y^2)

(1/y) +(2/7) -(3/2y^2)=0 multipli bi y^2...y +(2/7)y^2 -(3/2)=0 or 14*(2/7)y^2 +14y -14*(3/2)=0 4y^2 +14y -21=0 or (x-1.1331406)(x+4.6331406)=0
Read More: ...

Tips for a great answer:

- Provide details, support with references or personal experience .
- If you need clarification, ask it in the comment box .
- It's 100% free, no registration required.
next Question || Previos Question
  • Start your question with What, Why, How, When, etc. and end with a "?"
  • Be clear and specific
  • Use proper spelling and grammar
all rights reserved to the respective owners || www.painphr.com || Terms of Use || Contact || Privacy Policy
Load time: 0.1153 seconds